Analysis of Associated Factors Breast Canser in Women at Pirngadi Hospital Medan in 2020 - Sari, Hayatur Ridha (Asian Journal of Social and Humanities, 2023)
WHO show breast canser is the most cases in Indonesia, namely 58,256 (16,7%) case of the total 348,809 cases of canser. The research objective was to analyze the factors associated with breast canser. The research was an analytic survey with a cross sectional approach. The population was 99 respondents who experienced breast canser in January-July 2020. The sample were 30 respondents as outpatient of Oncology Surgical Clinic Of Pirngadi Hospital Medan. The results showed that there was a relationship between age (p=0,0000), parity (p=.005), age at first menstruation (menarche) (p= .002), history of breast canser (p=.024), smoking habits (p=.024) and contraception (p=.005) with breast canser based on the result of the chi square test with p-value <.05. and the results of the multivariate analysis of the dominant factors were the variable age at first menstruation (menarche) with a significant value of .005 (p-value .05), the value of the B coefficient of 3.555 was positive, and the use of contraceptives with a significant value of.009 (p-value <.05), the value of the coefficient B, was 3.219 was positive. The conclusion showed a relationship between age, parity, age at fierst menstruation (menarche), history of breast canser, smoking habits, and use of contraceptives were found.